Using modelling approaches to understand the implications of physiological challenges and raw material demands on aquaculture feed designs - D. Glencross, Brett (Facultad de Ciencias Biologicas, 2010)
Models have been used for sometime in estimating fish production and nutrient/energy demands. One form of these models, the factorial bioenergetic model, is described here and several potential applications from it explored. One such application is the examination of the effects of heat-stress on barramundi (Lates calcarifer) bioenergetics. These were examined using a modelling approach to explore the implications of the key model parameters and subsequently a redefined model was designed. Using the redefined factorial model the optimal iterative feed specifications were then redefined for a range of fish sizes at temperatures of 25°C, 30°C and 35°C. A feed demand model was also developed based on the demand for digestible energy at each of these temperatures. The model outputs suggest that at high temperatures (35°C) that there is an increase in the ratio of digestible protein to digestible energy required and that with increasing size there is a decrease in the digestible protein to digestible energy demand. These model outputs have been independently evaluated in empirical experiments and provide evidence consistent with the model. The use of such a factorial feed demand model also allows for the examination raw material demands over the full production cycle of the fish. By following total feed demand and then overlaying least-cost formulations both with and without fishmeal/oil replacement options it becomes possible to highlight periods of high demand and issues associated with different formulation strategies. The use of such modelling approaches provides a useful tool to identify those strategies that should be followed up with practical empirical research.